The financial crisis, oil price hike, the Arab spring and foreign demand for Filipino workers - Edita A. Tan (University of the Philippines, School of Economics (UPSE), 2012)
The paper inquires into the impact of contemporary major world events - the recession in the United States and Western Europe, the oil price hike, and the Arab Spring - on the flow of overseas Filipino workers or OFWs and their remittances. The paper finds that the recession in the West has not spread worldwide for its share in world trade has declined significantly since the 1980s. The oil exporting countries gained from the oil price hike and there are now many more economies that have achieved appreciable growth which they have been able to sustain up to the present, e.g. the Asian tigers, BRICs, Botswana. On the other hand, Tunisia, Egypt, Libya and Syria are minor employers of Filipino workers. Expectedly, the varied economic performance of the world economies has had differential impact on demand for migrant workers. The OFWs have found employment in varied occupations in varied destinations with the large majority in the Middle East and East Asia which have not been negatively affected by the Western recession. Many are also in service occupations that did not suffer as much decline in demand as in other occupations. The paper provides some empirical support to these findings.
Keywords: 330; Weltkonjunktur; Finanzkrise; Politische Unruhen; Arabische Staaten; Rücküberweisungen; Philippiner; Erwerbstätigkeit; Auslandsaufenthalt; Philippinen